2012
DOI: 10.1590/s0037-86822012000200028
|View full text |Cite
|
Sign up to set email alerts
|

Challenge in the management of infective endocarditis with multiple valvular involvement

Abstract: We describe the case of a 41-year-old man with congenital heart disease and infective endocarditis (IE), who presented multiple vegetations attached to the pulmonary, mitral, and aortic valves. Three valve replacements were performed, but the patient developed an abscess at the mitral-aortic intervalvular fibrosa and died due to sepsis. We briefly discuss the indications for surgery in IE, emphasizing its role in the treatment of uncontrolled infection. Keywords: Infection. Endocarditis. Surgery. Valves. RESUM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Right-sided IE accounts for 5-10 % of cases of IE [19], and it may occur in patients with a permanent pacemaker, implantable cardioverter defibrillator, CVC, or congenital heart disease, although this situation is more common in IVDAs [24]. Among the pathophysiological hypotheses that support the incidence of right-sided IE in IVDAs are abnormalities on the immune system, contaminated drug solutions and reduced injection hygiene [25].…”
Section: Introductionmentioning
confidence: 99%
“…Right-sided IE accounts for 5-10 % of cases of IE [19], and it may occur in patients with a permanent pacemaker, implantable cardioverter defibrillator, CVC, or congenital heart disease, although this situation is more common in IVDAs [24]. Among the pathophysiological hypotheses that support the incidence of right-sided IE in IVDAs are abnormalities on the immune system, contaminated drug solutions and reduced injection hygiene [25].…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of interest, one of our patients had a combined pulmonary and aortic valves IE. That is a very uncommon pathology [17,18] de Araújo [19] reported the case of aortic and pulmonary IE in a patient who was diagnosed as having VSD as well. It may be suggested that the presence of VSD was a very important factor for the etiology and pathogenesis because turbulent shunt flow could cause damage to the pulmonary valve endothelium.…”
Section: Discussionmentioning
confidence: 99%